2021
DOI: 10.3390/v13020158
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Bat Astroviruses (BtAstVs) among Bats in Poland: The Genetic BtAstVs Diversity Reveals Multiple Co-Infection of Bats with Different Strains

Abstract: Background: Astroviruses (AstVs) are common pathogens of a wide range of animal hosts, including mammals and avians, causing gastrointestinal diseases, mainly gastroenteritis and diarrhea. They prompt a significant health problem in newborns and young children and economic losses in the poultry sector and mink farms. Recent studies revealed a growing number of bat species carrying astroviruses with a noticeable prevalence and diversity. Here, we demonstrate the first detection of bat astroviruses (BtAstVs) cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Bat astroviruses are generally regarded as non-pathogenic for bats, but a recent study showed that Jamaican fruit bats, Artibeus jamaicensis, experience shifts in their gut microbiome towards increased pathogen-containing microbial genera, and may be more likely to contract co-infections after astrovirus infection [74]. Infections with two or more distinct astroviruses, as seen in one of our bat samples (21164-6), have been documented before-e.g., in a recent Polish study, where 5 out of 12 bats harboured multiple astroviruses, providing an opportunity for the recombination and emergence of new viruses [75]. Cross-species transmission and recombination between astroviruses of different species poses a risk to human and animal health, and is more common than previously thought [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Bat astroviruses are generally regarded as non-pathogenic for bats, but a recent study showed that Jamaican fruit bats, Artibeus jamaicensis, experience shifts in their gut microbiome towards increased pathogen-containing microbial genera, and may be more likely to contract co-infections after astrovirus infection [74]. Infections with two or more distinct astroviruses, as seen in one of our bat samples (21164-6), have been documented before-e.g., in a recent Polish study, where 5 out of 12 bats harboured multiple astroviruses, providing an opportunity for the recombination and emergence of new viruses [75]. Cross-species transmission and recombination between astroviruses of different species poses a risk to human and animal health, and is more common than previously thought [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Gregarious bats, for instance, often carry a variety of viral strains (e.g. [ 34 , 35 ].) and have been implicated as reservoirs of SARS-like CoVs [ 69 ] and sources of SARS-CoV-2 [ 70 ].…”
Section: Expected Impacts Of Co-infections On Microbial Communities: ...mentioning
confidence: 99%
“…Rodents, bats, primates and birds spearhead the list of diverse zoonotic vectors and reservoirs with regular interactions with humans as we further encroach on their natural habitats [63,64]. Moreover, these taxa are often highly co-infected [31,35,[65][66][67]. Infections in wildlife are likely so common that an uninfected state may prove itself to be a rare circumstance [65].…”
Section: Box 1: Tracking Changes In Microbiomes From Wild Animals Is ...mentioning
confidence: 99%
See 2 more Smart Citations